The Diagnostic Accuracy of Electrocardiogram in Differentiating Takotsubo Cardiomyopathy in Patients Presenting as Anterior Wall St-Segment Elevation Myocardial Infarction and Taking Coronary Angiography as Gold Standard - Muhammad Muneeb, Atta Ullah Khan Niazi, Zanib Javed Chatha, Ammar Hameed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Myocardial infarction: Myocardial infarction is the irreparable damage to heart muscles resulting in necrosis & is the leading cause of death; resulting in 500,000-700,000 important deaths related to the coronary artery occur each year. Cardiovascular disease is the most common reason resulting in premature mortality as well as morbidity among various ethnic group of white, black and Hispanic populations. Takotsubo Cardiomyopathy: TCM is a condition that affects the heart reversible syndrome, characteristic of decrease(hypokinesia)/ near absent movement (akinesia) of distal half of interventricular septum & cardiac apex showed as apical ballooning on echocardiogram with absence of an obstructive defect in epicardial coronary arteries following an emotional disturbance. Objective: To determine the diagnostic accuracy of electrocardiographic findings (elevation < 1mm Takotsubo cardiomyopathy can be identified in lead V1 in patients who have anterior wall ST-segment elevation myocardial infarction by taking coronary angiography as gold standard. Design: Cross-sectional survey Subjects & Methods: Using 250 incidences in the sample, and a 95% confidence level, a 13% error margin, and the anticipated percentage of Takotsubo cardiomyopathy i.e, 18% by using 74.2% sensitivity and 80.6% specificity of electrocardiographic findings i.e, ST-elevation of > 1mm in V1 in the detection of Takotsubo cardiomyopathy when myocardial infarction with ST-elevation in the anterior wall is the presenting symptom and coronary angiography as gold standard2. Results: The patients were 49 + 13 years old on average. Sensitivity & specificity of ECG criteria were 40.78% & 78.65%. The positive & negative predictive values were 43.28% & 76.5% respectively. Practical Implication: Our study showed negative association of ST-elevation of >1mm in ECG lead V1 to differentiate TC from anterior wall myocardial infarction. Further studies should be done to probe into the diagnostic accuracy of ECG in differentiating TC from acute anterior wall myocardial infarction. Conclusion: Electrocardiography is not diagnostic for distinguishing acute anterior wall pain from Takotsubo cardiomyopathy myocardial infarction so additional investigations need to be performed to diagnose the Takotsubo Cardiomyopathy. Keywords: Myocardial infarction, Takotsubo cardiomyopathy, Electrocardiogram, diagnostic accuracy Coronary angiography.